Use of complementary and alternative therapies for the treatment of dysmenorrhea among undergraduate pharmacy students in Malaysia: A cross sectional study - Abubakar, Usman; Zulkarnain, Amni Izzati; Samri, Fatihah; Ros Hisham, Sabrina; Alias, Anis; Ishak, Muhammad; Sugiman, Hajarah; Ghozali, Taufik (Springer Nature, 2020)
Background: Dysmenorrhea is a common problem that affects female students’ quality of life and academic activities. Complementary and alternative therapies (CATs) are used for the treatment of dysmenorrhea. This study investigated the practices and perceptions of female undergraduate students with dysmenorrhea towards CATs.